Coagulopathy and acute pancreatitis: pathophysiology and clinical treatment - Li, Lan; Tan, Qingyuan; Wu, Xueying; Mou, Xiaowen; Lin, Ziqi; Liu, Tingting; Huang, Wei; Deng, Lihui; Jin, Tao; Xia, Qing (Frontiers in Immunology, 2024)
Coagulopathy is a critical pathophysiological mechanism of acute pancreatitis (AP), arising from the complex interplay between innate immune, endothelial cells and platelets. Although initially beneficial for the host, uncontrolled and systemic activation of coagulation cascade in AP can lead to thrombotic and hemorrhagic complications, ranging from subclinical abnormalities in coagulation tests to severe clinical manifestations, such as disseminated intravascular coagulation. Initiation of coagulation activation and consequent thrombin generation is caused by expression of tissue factor on activated monocytes and is ineffectually offset by tissue factor pathway inhibitor. At the same time, endothelial-associated anticoagulant pathways, in particular the protein C system, is impaired by pro-inflammatory cytokines. Also, fibrin removal is severely obstructed by inactivation of the endogenous fibrinolytic system, mainly as a result of upregulation of its principal inhibitor, plasminogen activator inhibitor type 1. Finally, increased fibrin generation and impaired break down lead to deposition of (micro) vascular clots, which may contribute to tissue ischemia and ensuing organ dysfunction. Despite the high burden of coagulopathy that have a negative impact on AP patients' prognosis, there is no effective treatment yet. Although a variety of anticoagulants drugs have been evaluated in clinical trials, their beneficial effects are inconsistent, and they are also characterized by hemorrhagic complications. Future studies are called to unravel the pathophysiologic mechanisms involved in coagulopathy in AP, and to test novel therapeutics block coagulopathy in AP.